Epidemics, urban life, and sanitation :|Pera and the end of the plague - Karaağaçlıoğlu, Fezanur. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Istanbul had been struck continuously by plague epidemics ever since the Black Death broke out in 1347. This thesis is about Pera in the early nineteenth century which constitutes the last stage of the history of plague epidemics in Istanbul. The discussion includes Galata and only occasionally other neighboring districts as well. However, it focuses significantly more on Pera. The thesis attempts to sketch a landscape of disease and illustrate how Pera was experienced during the days of plague by examining contemporary European accounts. Indeed, Europeans stayed in Pera when they came to Istanbul, so their observations with regard to the city vis-à vis plague almost always relate to this district. Yet, there are several other factors that highlights Pera, especially from urban and cultural historical points of view. Escaping the plague in Galata counts among the reasons why Pera emerged as it did in the late sixteenth century. By the nineteenth century, it had already become a “plagued” place itself. A number of plague hospitals were active here in the examined period, and in the cemeteries, through which one would take promenades, one could see gravestones with epitaphs informing that the buried person died of plague. Besides, people with different responses to plague met each other here. In order to approach these accounts for a historical analysis, scholarly works on plague written from various perspectives are consulted. So, the actors, places, and traits of the district in the days of plague are identified and contextualized.
Keywords: Black Death -- Turkey -- History.; Plague -- Turkey -- Epidemiology -- History.; Turkey -- History -- Ottoman Empire, 1288-1918.